1995
DOI: 10.1039/c39950000931
|View full text |Cite
|
Sign up to set email alerts
|

Novel palladium-catalysed cyclodimerization of butadiene in the presence of carbon dioxide and water

Abstract: The first example is reported of a palladium-catalysed cyclodimerization of butadiene t o 2-vinylmethylenecyclopentane occurring in catalytic turnovers and yields far superior to the nickel-based systems, which are claimed t o be specific for cyclodimerization reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The combination of Pd and P(o-tolyl) 3 has been shown to mediate this transformation (eq 25). 90 This combination also mediates the dimerization of butadiene to afford a cyclopentane product in 52% yield at 90 • C. 91 Subjecting dienyne substrates to this combination in acetic acid/benzene at room temperature leads to an atom economical cycloisomerization to the corresponding tricyclic products (eq 26). 92 Both the "Metallo-Ene" cyclization and the "Metallo-Ene" carbonylation can also be catalyzed by Pd[P(o-tolyl) 3 ] 2 (Scheme 7).…”
Section: Cross-coupling Reactions Involving C-h Activationmentioning
confidence: 99%
“…The combination of Pd and P(o-tolyl) 3 has been shown to mediate this transformation (eq 25). 90 This combination also mediates the dimerization of butadiene to afford a cyclopentane product in 52% yield at 90 • C. 91 Subjecting dienyne substrates to this combination in acetic acid/benzene at room temperature leads to an atom economical cycloisomerization to the corresponding tricyclic products (eq 26). 92 Both the "Metallo-Ene" cyclization and the "Metallo-Ene" carbonylation can also be catalyzed by Pd[P(o-tolyl) 3 ] 2 (Scheme 7).…”
Section: Cross-coupling Reactions Involving C-h Activationmentioning
confidence: 99%
“…A variety of transition metal-catalyzed cycloaddition reactions are known; the [3 + 2] mode has been most extensively developed in metal-catalyzed reactions of trimethylene methane equivalents and methylene cyclopropane derivatives . The formation of 2-methylenevinylcyclopentane ( 9 ) from butadiene is known in nickel-catalyzed reactions; its formation is often reported in mixtures with [4 + 2] and [4 + 4] cycloadducts and linear dimers. Bergamini found that 9 could also be obtained via a palladium-catalyzed reaction of butadiene, but rather high temperatures and long reaction times were required (Scheme ). , 2,7-Octadienol can be obtained from the palladium-catalyzed linear dimerization of butadiene with trapping by water. Its carbonate derivative 10 undergoes palladium-catalyzed cyclization in acetic acid to also give 9 (65%), thus defining a three-step route from butadiene to 9 using palladium-catalysis to form each carbon−carbon bond.…”
mentioning
confidence: 99%